Targeted Trigonelline Derivatives as Anti-Diabetic Agents: In-Silico Evaluation of Drug-Likeness, Safety and Efficacy - Palak, Palak; Chauhan, Nikunj; Kumar Maurya, Pawan; Singhal, Shipra; Katiyar, Deepti; Prakash, Surya (Journal of Neonatal Surgery, 2025)
One of the most common metabolic disorders worldwide today is Type 2 diabetes mellitus. It is characterized by symptoms as a recognizable cause of metabolic distress, symptom and pathology. It is thought to be a heterogeneous and progressive group of disorder in which beta cell dysfunction is accompanied by lactic acidosis representing a number of metabolic pathways implicated in insulin metabolism and associated with cardiovascular pathophysiology. A high rate of diabetes-related mortality and morbidity is associated with it. Fenugreek, a spice, has been extensively used as an antidiabetic and hypolipidemic agent. It has also been used to treat diabetic complications, central nervous system (CNS) and cardiovascular (CVS) disorders. The pharmacological properties and mechanisms of a major alkaloid component of fenugreek- Trigonelline, have been thoroughly evaluated, especially with regard to its pharmacokinetics and toxicity. The present insilico study using CADD was designed to evaluate the useful effects of trigonelline hybrids against T2DM. Several amino acid derivatives of trigonelline were made and computational tools like Swiss ADME, Discovery studio Biovia and PyRx were used to evaluate the derivatives for binding affinity to key diabetic targets, drug likeness, ADME properties and potential off target effects. These findings paved the path for more preclinical and clinical research by indicating a final list of potent trigonelline-based compounds with promising anti-diabetic qualities. These results highlight trigonelline derivatives' potential as a new class of antidiabetic drugs and highlight the value of insilico approaches in the drug discovery process for complicated conditions like type 2 diabetes.